2019
DOI: 10.1371/journal.pone.0221635
|View full text |Cite
|
Sign up to set email alerts
|

A conditional inducible JAK2V617F transgenic mouse model reveals myeloproliferative disease that is reversible upon switching off transgene expression

Abstract: Aberrant activation of the JAK/STAT pathway is thought to be the critical event in the pathogenesis of the chronic myeloproliferative neoplasms, polycythemia vera, essential thrombocythemia and primary myelofibrosis. The most frequent genetic alteration in these pathologies is the activating JAK2V617F mutation, and expression of the mutant gene in mouse models was shown to cause a phenotype resembling the human diseases. Given the body of genetic evidence, it has come as a sobering finding that JAK inhibitor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Indeed, Gli1 + or LepR + MSCs have been identified as fibrosis-driving myofibroblasts in the context of JAK2 pathway mutations [92][93][94] , but it remains to be determined whether MYC in HSCs can also activate Gli1 + or LepR + MSCs. Third, consistent with observations from other MPN mouse models [95][96][97][98][99][100][101] , we observed significant fibrosis in the spleen and liver, but less in the BM in MYC-driven murine MF. While it is possible that inherently higher levels of S100A8/A9 in the normal mouse BM niche vs. human BM reflect a tolerability of higher S100A8/A9 levels in murine BM before fibrosis occurs, other differences in the BM niche between mouse and human, as well as between mouse BM and spleen, also need to be explored as potential explanations for the differences in fibrosis phenotypes.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, Gli1 + or LepR + MSCs have been identified as fibrosis-driving myofibroblasts in the context of JAK2 pathway mutations [92][93][94] , but it remains to be determined whether MYC in HSCs can also activate Gli1 + or LepR + MSCs. Third, consistent with observations from other MPN mouse models [95][96][97][98][99][100][101] , we observed significant fibrosis in the spleen and liver, but less in the BM in MYC-driven murine MF. While it is possible that inherently higher levels of S100A8/A9 in the normal mouse BM niche vs. human BM reflect a tolerability of higher S100A8/A9 levels in murine BM before fibrosis occurs, other differences in the BM niche between mouse and human, as well as between mouse BM and spleen, also need to be explored as potential explanations for the differences in fibrosis phenotypes.…”
Section: Discussionsupporting
confidence: 91%
“… 56 Conditionally inducible JAK2V617F mouse models in which JAK2V617F expression can be switched off and the MPN phenotype is reversed support this approach. 73 , 74 Type II JAK2 inhibitors that bind JAK2 in an inactive conformation have been developed and reported to show enhanced selectivity for mutant JAK2 in preclinical models. 75 , 76 Targeting ubiquitination and degradation of mutated JAK2 is another novel approach to JAK2 inhibition currently under investigation, including design of proteolysis-targeting chimeras that degrade oncogenic JAKs and inhibition of deubiquitinases that stabilize the JAK2V617F protein.…”
Section: Jak2 Inhibition In Mpnsmentioning
confidence: 99%
“…Presence of wildtype HSCs, derived from the wildtype competitor bone marrow, can maintain hematopoiesis when MPN HSCs are effectively targeted by new therapeutic approaches. Transgenic mouse models with reversible on-off JAK2-V617F expression 29 , could serve as a the ideal positive controls for drugs that are selective for the mutant JAK2 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…When constitutive VavCre was used activate the JAK2-V617F transgene, ET phenotype was observed and was associated with lower JAK2-V617F expression levels in bone marrow, whereas PV phenotype resulted when conditional MxCre or SclCre was used activate the transgene, leading to higher JAK2-V617F expression 27,28 . Recently, transgenic mice expressing Jak2-V617F under the tetracyclin dependent SCL-tTA-2S tet-off system were generated 29 . Using this system, the authors showed that turning on Jak2-V617F expression resulted in MPN phenotype and turning off Jak2-V617F reversed the phenotypic features, indicating that mutant selective JAK2 inhibitors should profoundly disable the JAK2-V617F MPN clone.…”
Section: Mouse Models Of Mpnmentioning
confidence: 99%